The Role Of Nalanda Students As Buddhist Religious Education Teachers In Influenced Buddhist Pancasila Values - Ratna Pudi Chinsia; Ida Ayu Gde Yadnyawati; Sulan (PT. Padang Tekno Corp, 2026)
The background of this study is based on the increasing tendency of deviant behavior and delinquency among elementary school students, which demands an early approach to character education. Nalanda students who serve as Buddhist Religious Education teachers have a strategic role in shaping the character and behavior of students through the internalization of Buddhist Pancasila values, which are expected to prevent potential delinquency and foster students who are morally and spiritually grounded. This study aims to analyze the roles, effectiveness, and strategies employed by Nalanda students in instilling Buddhist Pancasila values in elementary schools as a preventive effort against juvenile delinquency. This research applies a qualitative approach with a descriptive method. The study was conducted at Mutiara 17 August Elementary School, Edelweiss School, and Bina Pelita Bangsa Elementary School. Data were collected through in-depth interviews, observations, and documentation involving Nalanda students, principals, and homeroom teachers in five elementary schools. The data analysis technique employed was the interactive model of Miles and Huberman. The results reveal that Nalanda students act as value educators by instilling principles such as loving-kindness (mettā), responsibility, discipline, and respect for parents and teachers. The strategies used include role modeling, habituation in Buddhist spiritual practices, integration of values in learning, and personal approaches to students. The effectiveness of these roles is reflected in students' behavioral changes, such as becoming more orderly, polite, and the declining incidence of violations and social conflicts. The role of Nalanda students as Buddhist Religious Education teachers has proven to contribute significantly to the prevention of juvenile delinquency through character education based on Buddhist Pancasila values.